1997
DOI: 10.2166/wst.1997.0098
|View full text |Cite
|
Sign up to set email alerts
|

Wet air oxidation: kinetics of reaction, carbon dioxide equilibrium and reactor design - an overview

Abstract: Aqueous wastes containing organic pollutants can be efficiently treated by wet air oxidation (WAO), i.e. oxidation by molecular oxygen in the liquid phase, under high temperature (200 to 325°C) and pressure (up to 150 bar). In western Europe, only an handful of industrial plants are in operation. Most of them were designed by extrapolating results from pilot plants. Only a very few studies have been devoted to the scientific design of such reactors (bubble columns). This paper discusses what needs to be known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Even though this process is similar to the conventional WAO processes employed in the regeneration of spent activated carbons [21][22][23] and in the destruction of organic contaminants in liquid streams, [24][25][26] its main purpose is very different because our goal is to synthesize a valuable material in a controlled environment. Some studies of WAO of carbon have been reported, [26][27][28][29] but most are concerned with the kinetics of the oxidation of adsorbed species on the carbon instead of the carbon itself. Charest and Chornet 21 described a detailed kinetic study of WAO of virgin activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this process is similar to the conventional WAO processes employed in the regeneration of spent activated carbons [21][22][23] and in the destruction of organic contaminants in liquid streams, [24][25][26] its main purpose is very different because our goal is to synthesize a valuable material in a controlled environment. Some studies of WAO of carbon have been reported, [26][27][28][29] but most are concerned with the kinetics of the oxidation of adsorbed species on the carbon instead of the carbon itself. Charest and Chornet 21 described a detailed kinetic study of WAO of virgin activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Past WAO studies have shown that pH has a significant effect on the WAO reaction pathway 8 and is one of the most important parameters in WAO reactor design. 11 Acidic conditions might significantly enhance the WAO of LAS, as aromatic sulfonates can be hydrolytically desulfonated in the presence of high concentrations of mineral acids via reaction 1 12 Thus, if a mineral acid is added, reaction 1 is catalytically accelerated, increasing in rate 2.5-3 times for every 1 M rise in acid in the solution or for every 10 °C rise in temperature. 12 Phosphoric acid is the most widely used desulfonation catalyst, despite being the least active.…”
Section: Introductionmentioning
confidence: 99%